1999
DOI: 10.2337/diacare.22.7.1059
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight of women with gestational diabetes.

Abstract: After adjustment for the gestational age of delivery, women with GDM do not themselves have either a lower or higher birth weight than a matched group. These data suggest that women with GDM are either not a good surrogate for investigating the relationship between birth weight and type 2 diabetes or that correction for the gestational age of delivery removes the most important confounding variable. It is also possible that modern dietary changes may have altered the relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…This risk increase is, if anything, underestimated, since some of the 205 cases among the controls with maternal diabetes diagnosis might have had diabetes type 2 or GDM. The results of this study are in concordance with most of the studies carried out in the field during recent years (13 Á16), with the exception of one study (17).…”
Section: Discussionsupporting
confidence: 91%
“…This risk increase is, if anything, underestimated, since some of the 205 cases among the controls with maternal diabetes diagnosis might have had diabetes type 2 or GDM. The results of this study are in concordance with most of the studies carried out in the field during recent years (13 Á16), with the exception of one study (17).…”
Section: Discussionsupporting
confidence: 91%
“…In 1999, a small Australian study by Moses et al 18 , examining pregnant women referred for medical management of their gestational diabetes mellitus, found that the mean 2-h glucose concentration at diagnosis of gestational diabetes mellitus presented a U-shaped association when women with gestational diabetes mellitus had been analyzed apart as three groups -small for gestational age, adequate for gestational age and large for gestational age. Among women diagnosed with gestational diabetes mellitus, the 2-h glucose level was higher among the small for gestational age group than in the adequate for gestational age group, which could suggest a higher insulin resistance between the small for gestational age women, however the association was not statistically significant.…”
Section: Birth Weightmentioning
confidence: 99%
“…risk for GDM as a pregnant adult. 13,14 The results of these studies are conflicting, and interpretation of findings is limited by small sample sizes, 13 failure to evaluate dose-response associations, 13 lack of information on prepregnancy body mass index (BMI), 14 and possible bias due to self-reported outcomes. 14 In this article, we describe findings from a large, population-based study that addresses these concerns.…”
mentioning
confidence: 99%